Pengaruh Dana Pihak Ketiga dan Giro Wajib Minimum terhadap Return on Assets pada Bank Umum Konvensional - Hurriyani Elvira; Dadang Hermawan; Hasbi Assidiki Mauluddi (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This aim of this research are to analyze the effect of Third Party Funds (TPF) and Reserves Requirements (RR) on Return on Assets (ROA) at Conventional Commercial Banks Listed on Indonesia Stock Exchange (BEI) period 2015-2018. The population on this research are Conventional Commercial Banks Listed on Indonesia Stock Exchange period 2015-2018. The samples use were 12 banks, the samples on this research is using the purposive sampling method or the samples were taken by certain criteriaThe analysis used to determine the effect of Third Party Funds (TPF) and Reserves Requirements (RR) on Return on Assets (ROA) is verificative analysis using the help of Eviews 10 software. The results of this study indicate that the TPF and RR simultaneously have a significant effect on ROA. TPF has a positive and partially significant effect on ROA, while RR has a positive and partially insignificant effect on ROA.